Perkawinan Anggota Lembaga Dakwah Islam Indonesia Menurut Hukum Perkawinan Islam - Listyorini, Indah; Dyana, Burhanatut; Candra Pramudya, Ree Naldy (Qanun: Jurnal Hukum Keluarga Islam, 2023)
The Indonesian Islamic Da'wah Institute (LDII) group in Bojonegoro Regency strictly adheres to the rules within its organization. It is prohibited to marry someone from a different organization or other than a member of the Indonesian Islamic Da'wah Institute (LDII). The aim of this research is to find out what the legal form of marriage is for members of the Indonesian Islamic Da'wah Institute (LDII) in Bojonegoro Regency. This research is field research, using a qualitative approach. By using primary and secondary data. The data that has been obtained is then processed using the theories of marriage, kafaah and Islamic law. The results of research on the form of marriage for members of the Indonesian Islamic Da'wah Institute (LDII) in Bojonegoro Regency according to Islamic law is the same as the marriage of other Muslim members, namely harmony and the conditions for marriage are the same as in general, there is a bride and groom, guardian, two witnesses and a qobul consent. Meanwhile, the Koran and Hadith are the basis. Members of the Indonesian Islamic Da'wah Institute (LDII) prefer people from the same group or organization because there is a sense of comfort in their own hearts, which is hoped by all the kufu' in terms of the organization, it can create harmony in the household later because there is a common understanding.